Environmental factors that influence wildfire protective-action recommendations. (1st January 2014) - Drews, Frank A.; Musters, Adrian; Siebeneck, Laura K.; Cova, Thomas J.
Each year wildfire incident commanders (ICs) manage thousands of events throughout the USA that often threaten life and property. In this task they make important decisions to protect both firefighters and citizens, usually under time pressure and uncertainty. Many environmental factors affect the choice and timing of the most effective protective-action in this context (e.g., evacuate, shelter-in-refuge, shelter-in-place). The goal of this research is to identify the critical factors that influence wildfire protective-action recommendations (PARs) and their relative importance. Forty-seven ICs from the western USA were surveyed to produce mean factor-importance scores, where multi-dimensional scaling (MDS) and pathfinder analysis were applied to visually assess factor similarity. The results indicate that more experienced ICs place greater importance on dynamic, fire-related factors, while also differing in their cognitive representation of these factors from less experienced ICs. These results have important practical implications in developing effective training interventions, supporting the process of sense-making, and designing decision support systems.